Under noise: sonic clues, wanderings, detours and obstacles (Palíndromo, 2025)
In this text, I present various moments of the the unfolding of my artistic practice, in a journey that begins in the 1980s and extends to the current period. It highlights the importance of conceptual elaboration as one of the working tools of contemporary artists, when conducted in close proximity to the material formulations at play and the formal solutions adopted. At each moment, we try to emphasize the presence of sound layers, whose activation is always significant and relevant within the ongoing actions. The artistic actions are taken as ‘noisy’, always implying a variety of sonic solutions and different ways of listening.
Keywords: Contemporary art; Sound Art; 1980s art; Bioconceptualism; artist-etc